An Analysis on Syntactic Complexity In Students’ Writing Skill at Eleventh Grade of SMAN 19 Kabupaten Tangerang in Academic Year 2019/2020 - Sutiah, Tia; Isnaniah, Isnaniah (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2020)
Abstract The aim of this researcIsnah is to find out the result of students' writing skill in using of syntactic complexity on essay descriptive text writing at 11th grade of SMAN 19 Kabupaten Tangerang. The total population is 290 students of eleventh grade and the sample is 33 students at XI IPA 2. This research used qualitative method, then sentences in writing skill that would be analyzed by the researcher are the sentences. The sentences are simple sentence, compound sentence, complex sentence, and compound-complex sentence. After the reseacher has done the analysis and calculated the total percentage of four the sentences. The result show essay in the simple sentence is 31%, compound sentence is 5%, complex sentence 7% and compound-complex sentence is 1% with percentage 33 students who got in learning syntactic complexity in the descriptive text. Keywords: Writing Skill, Syntactic Complexity, Descriptive Text